If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w(5w + 3) = 0 Reorder the terms: 2w(3 + 5w) = 0 (3 * 2w + 5w * 2w) = 0 (6w + 10w2) = 0 Solving 6w + 10w2 = 0 Solving for variable 'w'. Factor out the Greatest Common Factor (GCF), '2w'. 2w(3 + 5w) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'w' equal to zero and attempt to solve: Simplifying w = 0 Solving w = 0 Move all terms containing w to the left, all other terms to the right. Simplifying w = 0Subproblem 2
Set the factor '(3 + 5w)' equal to zero and attempt to solve: Simplifying 3 + 5w = 0 Solving 3 + 5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5w = 0 + -3 5w = 0 + -3 Combine like terms: 0 + -3 = -3 5w = -3 Divide each side by '5'. w = -0.6 Simplifying w = -0.6Solution
w = {0, -0.6}
| 2(x+2)3x=2(x+1)+1 | | 2[2(3-5x)+4]=5[2(3-3)+2] | | 30-5(6x+5)= | | 1-6x=6-x | | -4(2x+11)=11 | | 2x+45=x-5 | | x^3+7x^2-9x=63 | | x^2+27x+6=0 | | y^2+18y+13=-4 | | -2(y+3)=2y+3 | | x/2+16=77 | | 2(4+4r)+3r=63 | | y^3-7y^2+10=0 | | c/2+16=77 | | 3d-24-5=9b+18+1 | | 2(4+4r)+3=63 | | 7n^2-14n+54=-5 | | 13+17y-3(y+11)= | | 5n+3=9 | | -7=-11+x/5 | | -t+2=10 | | 6y-9y=-16-20 | | 5b^2=-12 | | 55-40=30 | | -8x-2-9x-1=4 | | 14x+13-8x-1= | | 10=1x+2 | | (3x^2-3x-2)+(3x^2+4x-3)= | | 2(3-4k)=-51+3k | | 3(3x-2)-13=4x-4 | | 10+2x+2x+x=3000 | | 3+3+(2d-5)+(2d-5)=2+2+(2d-4)+(2d-4) |